An adjoint sensitivity study of chlorofluorocarbons in the North Atlantic - Li, Xingwen; Wunsch, Carl (Journal of Geophysical Research, 2004)
Author Posting. © American Geophysical Union, 2004. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Journal of Geophysical Research 109 (2004): C01007, doi:10.1029/2003JC002014. Adjoint sensitivities of CFC-11 concentrations and CFC-11/CFC-12 ratio ages in a North Atlantic general circulation model are analyzed. These sensitivities are compared with those of spiciness, T − (β/α) S, where α, β are the thermal and haline expansion coefficients, respectively. High-sensitivity fields are candidates for providing the most powerful constraints in the corresponding inverse problems. In the dual (adjoint) solutions all three variables exhibit the major ventilation pathways and define the associated timescales in the model. Overall, however, spiciness shows the highest sensitivity to the flow field. In the North Atlantic Deep Water, sensitivities of CFC properties and spiciness to the isopycnal mixing and thickness diffusion are of the same order of magnitude. In the lower subtropical thermocline, sensitivities of CFC properties to the isopycnal mixing and thickness diffusion are higher. The utility of this sensitivity is undermined by the need to reconstruct their boundary conditions. Given the influence of T, S measurements on the density field, they produce the most powerful constraints on the model on the large scale. It still remains possible, however, that transient tracers can provide a larger relative information content concerning the mixing process between the near-surface boundary layer and the thermocline but dependent upon the ability to reconstruct accurate initial and boundary conditions. This work was supported by NSF Award OCE-9730071, OCE-9617570, NASA Award NAG5-7857 and NAG5- 11933.